Health care utilisation in Cox’s Bazar district, Bangladesh, during the first year of the COVID-19 pandemic: A mixed-methods study among host communities - Chiara Altare; Natalya Kostandova; Md Abul Hasan; Jogie Abucejo Agbogan; Md Lalan Miah; Hannah Crockett; Madison Bates; Sharon Leslie; Brigitte Tonon; Caroline Antoine; Paul Spiegel (Global Public Health)
To respond to the COVID-19 pandemic, countries introduced public health and social measures that had indirect societal, economic consequences. Concerns during epidemics include continuity of routine health services. We investigate how healthcare utilisation and healthcare seeking behaviour changed during the first year of the COVID-19 pandemic among host communities in Cox’s Bazar, Bangladesh. This mixed-methods study combines quantitative analyses of routine health data and population-based findings about healthcare seeking behaviours. Trends in consultations changed according to facility level (higher-level facilities included Upazila Health Complexes and District Hospitals; lower-level facilities included Community Clinics and Union Health and Family Welfare Centers). At the pandemic’s beginning, drops were seen at higher-level health facilities for outpatient department (OPD) consultations, respiratory infections, and antenatal care. Minor reductions or increases were seen at lower-level facilities for the same services. Half of the subdistricts reported a cumulative increase in OPD and respiratory tract infection consultations. Most subdistricts reported a cumulative decrease in antenatal care. Child vaccinations dropped in all subdistricts, half of which did not catch-up, resulting in a cumulative decrease of delivered doses. Fear of contracting COVID-19 and financial constraints were the main reasons for decreased access. Drivers of healthcare seeking behaviours should be better understood to guide preparedness and service delivery modalities at primary and secondary levels.